Online Learning for Dummies illustrations - Manning, Susan; Johnson, Kevin E. 1972- (For dummies, 2021)
"Whether you're a college student, adult learner, or professional in continuing education, some--and sometimes all--of your learning will happen in a virtual classroom. This book is your friendly guide to the fast-growing possibilities of this world, from choosing the right course and mastering the software to polishing up your online communication and study skills. Whatever you want from your study experience--school success, professional development, or just pursuing your passion--this is your road map to online educational success!"--Page 4 of cover.